Sosialisasi Pengelolaan Sampah Metode 3R (Reduce, Reuse, Recycle) di Kelurahan Tinambung Kabupaten Polewali Mandar - Zul Asriana; Astinawaty Astinawaty (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Tinambung Village is the center of trade and services in Tinambung District. In general, trade and service businesses are activities that involve buying and selling goods and/or services between traders and buyers. In the trade and service area, problems certainly arise, one of which is the problem of waste. Therefore, we conduct community service in the form of socialization regarding waste management using the 3R method, namely Reduce, Reuse, and Recycle in Tinambung Village, Polewali Mandar Regency. This activity is in the form of socialization regarding waste management using the 3R method, namely Reduce, Reuse, and Recycle in Tinambung Village, Polewali Mandar Regency. Community service activities begin with an evaluation by filling out a questionnaire to determine the level of understanding of the Tinambung Village community regarding the 3R concept. and the results are still many participants who do not know or are not familiar with the 3R concept. Then, socialization is carried out to provide an understanding of the 3R concept to participants. After that, organic waste processing practices were carried out, namely by making compost. This socialization activity to the community is not only to introduce 3R-based waste management, but also to teach the community how to directly practice managing waste according to the 3R method